2023
DOI: 10.3390/healthcare11142031
|View full text |Cite
|
Sign up to set email alerts
|

Anger and Aggression in Relation to Psychological Resilience and Alcohol Abuse among Health Professionals during the First Pandemic Wave

Argyro Pachi,
Evgenia Kavourgia,
Dionisios Bratis
et al.

Abstract: Mental health problems, behavior changes, and addictive issues have been consistently documented among healthcare workers during the pandemic. The objective of this study was to investigate the levels of anger and aggression in relation to psychological resilience and alcohol abuse among healthcare workers during the first wave of the COVID-19 pandemic. A total of 120 physicians and 123 nurses completed an online survey of the Dimensions of Anger Reactions-5 (DAR-5), the Brief Aggression Questionnaire (BAQ), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 184 publications
(190 reference statements)
0
4
0
Order By: Relevance
“…As to the gendered aspect of resilience, most studies support that males scored higher resilience levels compared to females, apart from reasons of heritability [117] , [118] . Gender-specific differences regarding resilience levels were not observed in our previous study on nursing staff during the pandemic [48] . In addition, since results from other studies have been equivocal, gender has been identified as an inconclusive and unreliable factor in predicting resilience.…”
Section: Methodological Issues and Limitations Of This Studycontrasting
confidence: 70%
See 3 more Smart Citations
“…As to the gendered aspect of resilience, most studies support that males scored higher resilience levels compared to females, apart from reasons of heritability [117] , [118] . Gender-specific differences regarding resilience levels were not observed in our previous study on nursing staff during the pandemic [48] . In addition, since results from other studies have been equivocal, gender has been identified as an inconclusive and unreliable factor in predicting resilience.…”
Section: Methodological Issues and Limitations Of This Studycontrasting
confidence: 70%
“…With a target population of 27103 nurses [19] , [21] , [24] , at a confidence level of 95%, a margin of error of 5% and a percentage of our sample picking a particular answer of 50%, the adequate sample of nurses was set at 379 participants. Considering that the response rate in past studies [48] , [49] was more than 60%, a total of 600 email invitations were dispatched, with 433 nurses consenting to participate, resulting in a response rate of 72.2%. In the first 7 days we had received over 80% of the responses.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the personality dimension of psychoticism was highlighted as an important predictor of the probability of high depersonalization and low personal achievement scores, confirming previous reports [ 38 , 108 ]. Specifically, feelings within the psychotic spectrum, such as irritability and quick-tempered reactions, a tendency to be suspicious of others’ motives or actions, feelings of restlessness, and general inner tension are valid signs of less psychological resilience and are significantly associated with a higher likelihood of perceiving incompetence, unsuccessful outcomes in their work, and a cynical behavior toward colleagues and patients [ 109 ]. Further, the association between psychoticism and lower personal achievement and higher depersonalization may be more pronounced among intensivists due to the increased responsibility and decisional burden associated with their roles, documented to impact decreased job satisfaction and emotional and psychological burnout [ 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%